SSB Mahardika's Offensive Tactics - Giofandi Samin; Gilang Ramadan; Ardin Abdul Gani; Ratna Dewi; Iwan Fataha (JUARA : Jurnal Olahraga, 2022)
This study aims to produce a product development model for football attack tactics training at an early age and to increase the effectiveness of the ability to attack football tactics during competitions. This research is research and development carried out by adapting development research steps. This method begins with a needs analysis by developing an attack tactics training model with characteristics that match the results of the effectiveness test conducted at SSB Mahardika. Data were analyzed by descriptive quantitative on the rating scale. The number-based soccer attack tactic training model is used as a tool so that the players can increase their effectiveness against attacking abilities. Based on the results of the analysis in small group trials, it was found that the average choice was 76.67%; this stated that the attack tactics training model had a good category. In the large group trial, the middle option was 86.49%, which noted that the soccer attack tactics training model had a particular type. The soccer attack tactics training model based on the number of players is effective for increasing the ability of football tactics with a significance value of <0.05.